Greek Energy Communities: Maintaining a project’s sustainability within the context of energy exchange - Yfanti Sofia; Nikologiannis Marios; Viskadouros George; Markaki Marini; Iltsidis Stavros; Karapidakis Emmanuel (E3S Web of Conferences)
Sustainable energy practices have troubled policymakers, academics and entrepreneurs for several decades. The concept of Energy Communities (ECs) seems to gain ground throughout the globe as a means to mitigate climate and environmental crises and, in the same time, as a business opportunity within the energy domain. However, a literature survey can point out that this is not entirely true in several cases, even within the European Union. Such is the case for Greece; a south European country that even though, according to Green Tank’s mapping study in 2024, it appears to have roughly around 1,700 ECs, only very few of them are truly operational. According to the authors the participation to the energy exchange could serve as a catalyst towards financially feasible ECs investments. This paper uses actual production data and real quotes from material suppliers to investigate a potential expansion of an operational EC project located in Greece. The proposed installation estimates total profit of 7,904,811,224.22 EUR with an initial cost of 1,713,000 EUR.